Hubungan Penawaran Khusus Pada Tanggal Istimewa Terhadap Keputusan Pembelian Di Platform E-Commerce Shopee - Rolando, Benediktus; Rantetandung, Delizea Christy Disa; Winaya, Ni Nyoman Teristiyani (Malaqbi Publisher, 2024)
This research focuses on analyzing the relationship between special offers on special dates and purchasing decisions on the Shopee e-commerce platform. The selection of this topic is based on the increasing use of e-commerce among the community, particularly among students, who are often influenced by promotions and discounts offered on certain days. Special offers are expected to affect consumer behavior and boost sales. The research method used is a survey, with data collected through questionnaires distributed to students of the Digital Business Department, Semester 4, at Universitas Bunda Mulia. The results indicate a positive and significant relationship between special offers on special dates and purchasing decisions. These findings provide important insights for e-commerce companies in designing more effective and competitive marketing strategies, emphasizing the importance of leveraging special moments to attract consumer attention.